BIM investment, returns, and risks in China’s AEC industries - Jin, Ruoyu; Hancock, Craig Matthew; Tang, Llewellyn; Wanatowski, Dariusz (American Society of Civil Engineers, 2017)
Building information modeling (BIM), the emerging digital technology, is undergoing increasing application in developing countries including China. Both the governmental policy and industry motivation have indicated that BIM is becoming the mainstream innovation in China’s construction industry. Nevertheless, one major concern lies in the uncertainty of BIM investment for architecture, engineering, and construction (AEC) firms. Specifically, AEC firms should have the knowledge of areas BIM investment could focus on (such as BIM software); the expected returns from BIM investment; methods to enhance the returns from BIM usage; and the risks in implementing BIM. This study adopted a questionnaire survey–based approach to address these concerns related to BIM application and risk in China. BIM practitioners from multiple AEC fields and different experience levels were recruited as the survey sample. It was found from the questionnaire survey that both internal and external collaborations should be the BIM investment priority, together with the interoperability among multiple BIM software tools. Improved multiparty communication and understanding was the highest recognized return from BIM investment. Survey participants had a high expectation of BIM application in green building projects. Subgroup analysis conveyed the information that gaining BIM practical experience would provide professionals with more confidence on returns from BIM adoption in enhancing communication and understanding. Compared to survey participants from other professions, architects tended to have more conservative views on BIM’s effect on marketing their work, project planning, and recruiting/retaining employees. The findings from this empirical study provide an overview of BIM investment, return, and implementation-related risks for AEC professionals at different stages or levels of BIM practice, as well as suggestions for relevant public authorities when developing BIM guidelines (e.g., BIM applications in prefabrication construction). As an extension of existing BIM implementation studies in developed countries, this study provides insights of BIM practical experience and associated risks in China by adopting a holistic approach and summarizing the perceptions from AEC professionals across disciplines and experience levels. The knowledge gained from this study could be further applied in other developing countries where the application of information technology is growing in AEC projects.